2023
DOI: 10.2807/1560-7917.es.2023.28.34.2300409
|View full text |Cite|
|
Sign up to set email alerts
|

Cases of Crimean-Congo haemorrhagic fever in North Macedonia, July to August 2023

Dejan Jakimovski,
Krsto Grozdanovski,
Goran Rangelov
et al.

Abstract: The last report of Crimean-Congo haemorrhagic fever (CCHF) in North Macedonia was more than 50 years ago in the northwest. We report on a fatal CCHF case following a Hyalomma tick bite in the east of the country in July 2023. Tracing of 67 contacts identified CCHF in one healthcare worker (HCW) providing care for the patient. Monitoring of contacts is concluded (including further 11 HCW contacts), thus far 28 days after the death of the case no additional cases were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Up to 2010, an additional 12 human cases were recorded [ 98 ], none of which were fatal. More than 50 years after the first outbreak, a new fatal autochthonous case of CCHFV infection in a patient from the village of Kuchica, near Shtip, and a nosocomial infection in a healthcare worker who cared for the patient were described by Jakimovski et al [ 129 ]. Countrywide, serological studies conducted on sera collected from cattle [ 130 ], sheep and goats [ 131 ] revealed a high seroprevalence of CCHFV and widespread distribution of the virus in the country.…”
Section: North Macedoniamentioning
confidence: 99%
“…Up to 2010, an additional 12 human cases were recorded [ 98 ], none of which were fatal. More than 50 years after the first outbreak, a new fatal autochthonous case of CCHFV infection in a patient from the village of Kuchica, near Shtip, and a nosocomial infection in a healthcare worker who cared for the patient were described by Jakimovski et al [ 129 ]. Countrywide, serological studies conducted on sera collected from cattle [ 130 ], sheep and goats [ 131 ] revealed a high seroprevalence of CCHFV and widespread distribution of the virus in the country.…”
Section: North Macedoniamentioning
confidence: 99%
“…Although not the most prevalent tick-borne disease, Crimean-Congo hemorrhagic fever (CCHF) is one of the most concerning due to its severe and often fatal consequences in affected individuals, as well as its potential for pandemic spread under certain circumstances [7]. CCHF virus is widespread across Europe, Asia, and Africa [8][9][10]; however, it has never been reported in Australia and the Americas.…”
mentioning
confidence: 99%